Acetaminophen-induced toxicity is prevented by beta-D-glucan treatment in mice - VELİOĞLU ÖĞÜNÇ, AYLİZ; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ELSEVIER SCIENCE BV, 2006)
The protective effect of beta-glucan against oxidative injury caused by acetaminophen was studied in mice liver. BALB-c mice (25-30 g) were pretreated with beta-D-glucan (50 mg/kg, p.o.) for 10 days and on the 11th day they received an overdose of acetaminophen (900 mg/kg, i.p.). Four hours after the acetaminophen injection, mice were decapitated and their blood was taken to determine serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and tumor necrosis factor-alpha (TNF-alpha) levels. Tissue samples of the liver were taken for histological examination or for the determination of levels of malondialdehyde, an end product of lipid peroxidation; glutathione (GSH), a key antioxidant; and myeloperoxidase activity, an index of tissue neutrophil infiltration. The formation of reactive oxygen species in hepatic tissue samples was monitored by using the chemilummescence technique with luminol and lucigenin probes. Acetaminophen caused a significant decrease in the GSH level of the tissue, which was accompanied with significant increases in the hepatic luminol and lucigenin chemiluminescence values, malondialdehyde level, MPO activity and collagen content. Similarly, serum ALT, AST levels, as well as LDH and TNF-alpha, were elevated in the acetaminophen-treated group when compared with the control group. On the other hand, P-D-glucan treatment reversed all these biochemical indices, as well as histopathological alterations that were induced by acetaminophen. In conclusion, these results suggest that beta-D-glucan exerts cytoprotective effects against oxidative injury through its antioxidant properties and may be of therapeutic use in preventing acetaminophen toxicity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acetaminophen; beta-glucan; glutathione; lipid peroxidation; oxidative injury; tumour necrosis factor-alpha; STAPHYLOCOCCAL WOUND-INFECTION; INDUCED LIPID-PEROXIDATION; GUINEA-PIG MODEL; SUPEROXIDE ANION; OXIDATIVE STRESS; CYTOKINE RELEASE; REACTIVE OXYGEN; PROTECTIVE ROLE; FREE-RADICALS; IN-VITRO